The effect of cycling followed by running on respiratory muscle performance in elite and competition triathletes - Boussana, A.; Hue, O.; Matecki, S.; Galy, O.; Ramonatxo, M.; Varray, A.; Le Gallais, D. (European Journal of Applied Physiology, 2002)
This study investigated the possibility of there being differences in respiratory muscle strength and endurance in elite and competition triathletes who have similar maximal oxygen uptakes (O2max) and ventilatory thresholds (Thvent). Five internationally-ranked elite, [mean (SD) age 23.8 (1.4) years] and six nationally- and regionally-ranked competition [age 21.1 (1.1) years] male triathletes performed two successive trials: first an incremental cycle test to assess O2max and Thvent and second 20 min of cycling followed by 20 min of running (C-R) at intensities higher than 85% O2max. Cardioventilatory data were collected every minute during the two trials, using an automated breath-by-breath system. Maximal expiratory and inspiratory (PImax) strength were assessed before and 10 min after C-R from the functional residual capacity. Respiratory muscle endurance was assessed 1 day before and 30 min after C-R by measuring the time limit (tlim). The results showed firstly that during C-R, the competition triathletes had significantly (P<0.05) higher minute ventilation [mean (SEM) 107.4 (3.1) compared to 99.8 (3.7) l·min-1], breathing frequency [44.4 (2.0) compared to 40.2 (3.4) ·min-1] and heart rate [166 (3) compared to 159 (4) beats·min-1] and secondly that after C-R, they had significantly lower PImax [127.1 (4.2) compared to 130.7 (3.0) cmH2O] and tlim [2:35 (0:29) compared to 4:12 (0:20) min] than the elite triathletes. We conclude that, despite similar O2max and Thvent, the competition triathletes showed less extensive adaptive mechanisms, including those in the respiratory muscles, than did the elite triathletes. This led to higher ventilation, which appeared to be the cause of the faster development of fatigue in the inspiratory muscles in this group.